Assessment of the Efficacy of Home Remedial Methods to Improve Drinking Water Quality in Two Major Aquifer Systems in Jaffna Peninsula, Sri Lanka. (18th October 2017) - Wijeyaratne, W. M. Dimuthu Nilmini; Subanky, Suvendran
Abstract : Chunnakam and Vadamaradchi are two major aquifer systems in Jaffna Peninsula, Sri Lanka. This study was performed to compare water quality in the domestic wells in these aquifers and to assess the efficacy of household water treatments for treating contaminated water. Replicate well water samples were collected from each aquifer and pH, dissolved oxygen (DO), conductivity, total dissolved solids (TDS), salinity, temperature, total solids (TS), total hardness (TH), chemical oxygen demand (COD), oil and grease (OG), nitrate N (N), and total phosphate (TP) were measured. The sampled water from the domestic wells was filtered through commercial mineral filter and Moringa oleifera leaf powder and boiled at 100°C for 10 minutes and the TH, OG, N, and TP were measured. Both OG and N in Chunnakam were significantly higher and the DO were significantly lower than those of Vadamaradchi. TH, N, and OG of some wells exceeded the drinking water quality standards established by Sri Lanka Standards Institution. Moringa oleifera leaf powder filtration reduced N significantly and filtering through commercial mineral filter reduced OG, TH, and N significantly. Boiling at 100°C could remove TH significantly but may cause significant increase in N which might result in health impacts.